2013
DOI: 10.1007/s00128-013-1099-z
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fluoride from Contaminated Ground Water Using Raw and Modified Bauxite

Abstract: Endemic fluorosis affects millions of people worldwide. Fluorosis arises from the consumption of fluorine (F) contaminated water and was observed also in some parts of Turkey with volcanic rocks and geothermal resources. In the present study the removal of F from drinking water by raw and modified bauxite at the laboratory scale was investigated using a batch mode. Modified bauxite was prepared by using Na and Mg incorporated (B-Na, B-Mg) bauxite and calcination of Mg incorporated bauxite at 500°C (B-Mg-500). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Atasoy et al used raw and modified bauxite in fluoride removal and reached equilibrium after 3 hr. They found that the removal rate was fast at first, because all the absorption positions were empty and free fluoride ions were available (26). Evaluations of the effect of time on removal efficiency in the mentioned studies revealed results similar to those of the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Atasoy et al used raw and modified bauxite in fluoride removal and reached equilibrium after 3 hr. They found that the removal rate was fast at first, because all the absorption positions were empty and free fluoride ions were available (26). Evaluations of the effect of time on removal efficiency in the mentioned studies revealed results similar to those of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…By using fixed amounts of all bauxite samples, increasing the fluoride concentration from 2 to 6 mg/L increased the absorption capacity, but decreased the removal efficiency. A study by Atasoy et al showed that increasing the fluoride concentration from 1 to 10 mg/L reduced the removal efficiency from 66% to 36% (26). Lv et al used doublemodified hydroxides with polycarbonate, aluminum, and manganese in fluoride removal.…”
Section: Discussionmentioning
confidence: 99%
“…Because the changes in solution concentration were rather small after reaching equilibrium, the equilibrium time was used in the remaining adsorption studies. Atasoy et al [23] specified the similar phase for Fadsorption in the bauxite. It was mentioned that the changes in solution concentration were quite small after reaching equilibrium.…”
Section: Equilibrium Timementioning
confidence: 99%
“…It also results in less mineral content and more porosity in the teeth [6]. In addition, high fluoride concentration may cause skeletal fluorosis and serious problems in body [7][8][9][10]. As seen in studies in some parts of Turkey, fluoride concentration of water was found high from 1.5 to 13.7 mg/L due to the volcanic rocks and geothermal sources [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%